Identification of Cashew Pests in Jatisari Village, Jatisrono District, Wonogiri District - Octaviana, Dhea Cindy; Wiharti, Tri (Jurnal Biologi Tropis, 2025)
Cashew (Anacardium occidentale) is one of the export commodities with high economic value. However, cashew production in Indonesia faces serious challenges due to pest attacks that can reduce yields. This study aims to identify the types of pests that attack cashew trees in Jatisari Village, Jatisrono District, Wonogiri Regency, and to analyze the relationship between pest occurrence and environmental factors such as temperature, humidity, and rainfall. The method used in this study was direct observation in four hamlets with data collection through visual documentation and recording symptoms of pest attacks on plants. The results showed that there were 11 main pest species that attacked cashew, including Bemisia tabaci, Hyphantria cunea, Sanurus indecora Jacobi, Toxoptera citricidus Kirk., Helopeltis sp., Setothosea asigna, Orgyia definita, Euthalia aconthea, and Melanitis leda. These pests cause various forms of damage to plants, such as defoliation, flower and fruit drop, and stunted growth. Environmental factors such as temperature and humidity have been shown to have a significant impact on the level of pest infestation. This study provides insight for farmers in more effective and sustainable pest control efforts.